Pengaruh Model Pembelajaran Jigsaw Terhadap Hasil Belajar PAK Siswa - Lince Rauli Ture Simamora; Lilis Sulastri Manalu (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:This study aims to determine the effect of the Jigsaw Learning Model on students' PAK learning outcomes. With the hypothesis that there is a positive and significant effect between the Jigsaw Learning Model on students' PAK learning outcomes. .research population amounted to 125 people and research samples taken 36% totaling 45 people. Data were collected using a closed questionnaire of 39 items compiled by researchers based on variable indicators according to expert theory. .instrument testing was conducted on 37 students who were not research respondents whose validity and reliability had been tested..The results of data analysis show that there is a positive and significant effect with a coefficient of determination (r2) = 48.58% and a significant test of effect is obtained tcount ttable of 21.971.681, thus it can be concluded that H0 is rejected and Hα is accepted.Keywords: Jigsaw Learning Model, Students' PAK Learning Outcomes Abstrak:Penelitian ini bertujuan untuk mengetahui Pengaruh Model Pembelajaran Jigsaw terhadap Hasil belajar PAK siswa . Dengan hipotesis terdapat pengaruh yang positif dan signifikan antara Model Pembelajaran Jigsaw terhadap Hasil belajar PAK siswa . Populasi penelitian berjumlah 125 orang dan sampel penelitian diambil 36% berjumlah 45 orang. Data dikumpulkan dengan angket tertutup sebanyak 39 item yang disusun peneliti berdasarkan indikator variabel sesuai teori ahli. Uji coba instrumen dilakukan kepada 37 orang siswa yang bukan responden penelitian yang telah diuji validitas dan reliabilitasnya. Hasil analisis data menunjukkan bahwa terdapat pengaruh yang positif dan signifikan dengan koefisien determinasi (r2) = 48,58% dan uji signifikan pengaruh diperoleh thitungttabel sebesar 21,971,681, dengan demikian dapat disimpulkan H0 ditolak dan Hα diterima.Kata Kunci: Model Pembelajaran Jigsaw, Hasil Belajar PAK Siswa